Becoming Reading Group: reflections on assembling a collegiate, caring collective. Issue 3 (2nd July 2020) - Ey, Melina; Mee, Kathleen; Allison, Jai; Caves, Susan; Crosbie, Eliza; Hughes, Ainsley; Curtis, Faith; Doney, Rupert; Dunstan, Penny; Jones, Ryan; Tyndall, Adam; Baker, Tom; et al.
ABSTRACT: In neoliberalising universities, collegial and collective practices such as reading groups are often positioned by students, staff and managers as less important than meeting individual KPIs (such as producing research publications, seeking research grants, or meeting the increasing demands of producing quality teaching outcomes.) However, reading groups can be vital for cultivating caring collectives and spaces of collegiality. In this paper we use assemblage thinking to explore 25 years of a Geography reading group at the University of Newcastle. The paper addresses two questions: what does reading together do and make possible; and how might we think about the labours of reading together as a way of building caring collectives. The paper draws on reflections from 24 past and present members of reading group to explore how these kinds of academic practices nourish our working lives.